Electrophysiological Remodeling in Heart Failure - Wang, Yanggan (2010)
Heart failure affects nearly 6 million Americans, with a half-million new cases emerging each year. Whereas up to 50% of heart failure patients die of arrhythmia, the diverse mechanisms underlying heart failure-associated arrhythmia are poorly understood. As a consequence, effectiveness of antiarrhythmic pharmacotherapy remains elusive. Here, we review recent advances in our understanding of heart failure-associated molecular events impacting the electrical function of the myocardium. We approach this from an anatomical standpoint, summarizing recent insights gleaned from pre-clinical models and discussing their relevance to human heart failure.